2002
DOI: 10.1093/toxsci/70.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Half-Lives of Individual Polychlorinated Biphenyls and Serum Levels of 4-Hydroxy-2,3,3`,4`,5-pentachlorobiphenyl in the Rat

Abstract: This study was done to generate kinetic data on individual congeners of chlorinated biphenyls in the low dose range, which could be of value in the risk assessment procedure. Male Sprague-Dawley rats were given a single oral dose of a mixture of polychlorinated biphenyls (CBs) containing either CBs 105, 118, 138, 153, 156, 157, 170, and 180 (A-mix) or CBs 28, 52, 77, 87, and 101 (B-mix). Liver, serum, and adipose tissue were collected after 6 h up to 135 days, from rats given the A-mix, and after 6 h up to 4 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…In our primary cultured hepatocytes as well, conjugation of the OH-PCBs with glucuronic acid was contingent on PCB hydroxylation. These results support the findings by Oberg et al (2002) that in rats given a single oral dose of PCBs, the PCBs accumulate in large amounts in the liver immediately after uptake through the gastrointestinal tract and then recede drastically. Together with a growing body of research, our study has clarified that elimination of PCBs from the body depends on their hydroxylation and, in turn, on glucuronidation of the OH-PCB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our primary cultured hepatocytes as well, conjugation of the OH-PCBs with glucuronic acid was contingent on PCB hydroxylation. These results support the findings by Oberg et al (2002) that in rats given a single oral dose of PCBs, the PCBs accumulate in large amounts in the liver immediately after uptake through the gastrointestinal tract and then recede drastically. Together with a growing body of research, our study has clarified that elimination of PCBs from the body depends on their hydroxylation and, in turn, on glucuronidation of the OH-PCB.…”
Section: Discussionsupporting
confidence: 91%
“…Organ Tissues and UGT Isoforms Associated with OH-PCB Glucuronidation. In conjunction with the literature (Anderson et al, 1977;Norback et al, 1981;Oberg et al, 2002), our results indicate that hepatic as well as extrahepatic organ tissues can glucuronidate OH-PCB and that, as we suspected, the UGT isoforms are the isoforms largely responsible for the OH-PCB glucuronidation. UGT1A1, UGT1A6, and UGT2B1 are the isoforms predominantly governing OH-PCB glucuronidation, as disclosed by our tests on 10 OH-PCBs.…”
Section: Discussionsupporting
confidence: 90%
“…9−11 Competitive binding of OH-PCBs to TTR with T 4 leads to longer half-lives of the metabolites in the peripheral circulation and disrupts the action of thyroid hormone. 12,13 OH-PCBs have been detected in the blood of several wildlife species, 14−16 but the levels and patterns vary by species, possibly because of the species-specific difference in the metabolic potency of phase I CYP and/or phase II conjugation enzymes and binding affinity to TTR. 17,18 We have previously reported that high accumulation of DRCs induced CYP1A1, CYP1A2, CYP1B1, and CYP3A isozymes in the liver of wild Baikal seals, 19,20 implying the enhanced hepatic hydroxylation of dioxin-like (non-and mono-ortho) and nondioxin-like (di-, tri-, and tetra-ortho) PCBs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2). Typically, less-chlorinated PCBs (≤5 Cl) have a more rapid uptake (Oberg et al, 2002) and are more rapidly metabolized and eliminated (Matthews and Anderson, 1975;Oberg et al, 2002) than higher-molecular-weight congeners. Upon exposure, however, these compounds may be initially high in perfused tissue (Kania-Korwell et al, 2005) so that alewife from the ISC had a PCB profile indicative of parent PCB, e.g., Aroclor 1242.…”
Section: Discussionmentioning
confidence: 99%